The return of Frank James - Lang, Fritz, 1890-1976.; Fonda, Henry, 1905-1982.; Tierney, Gene.; Cooper, Jackie, 1922-; Hull, Henry, 1890-1977.; Carradine, John.; Bromberg, J. Edward, 1903-1951.; Meek, Donald, 1880-1946.; Collins, Eddie, 1883-1940.; Barbier, George, 1864-1945.; Tannen, Charles, 1915-1980.; Barnes, George, 1893-1953.; et al. (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2006)
Fabled Missouri outlaw Frank James, brother to the legendary Jesse James, straps on his six-shooters and rides out for revenge against his brother's killer.
Originally produced as motion picture in 1940.
Sequel to the film Jesse James.
Aspect ratio 1.33:1.
Director of photography, George Barnes ; editor, Walter Thompson ; musical direction, David Buttolph.
Henry Fonda, Gene Tierney, Jackie Cooper, Henry Hull, John Carradine, J. Edward Bromberg, Donald Meek, Eddie Collins, George Barbier, Charles Tannen.
DVD; NTSC; region 1; single layer.
Keywords: James, Jesse, -- 1847-1882 -- Drama; James, Frank, -- 1844-1915 -- Drama; Ford, Robert, -- 1862-1892 -- Pardon -- Drama; Ford, Charles Wilson, -- 1857-1884 -- Pardon -- Drama; Revenge -- West (U.S.) -- Drama; Outlaws -- West (U.S.) -- Drama; Criminal behavior -- West (U.S.) -- Drama; Brothers -- West (U.S.) -- Drama; West (U.S.) -- Drama; Western films; Biographical films; Feature films; Video recordings for the hearing impaired